Appraisal for organic amendments and plant growth‐promoting rhizobacteria to enhance crop productivity under drought stress: A review. (2nd May 2021) - Ullah, Naseer; Ditta, Allah; Imtiaz, Muhammad; Li, Xiaomin; Jan, Amin Ullah; Mehmood, Sajid; Rizwan, Muhammad Shahid; Rizwan, Muhammad
Abstract: Plants are sessile organisms, frequently face unfavourable growth conditions such as drought, salinity, chilling, freezing and high‐temperature stresses, inhibiting growth and development, and ultimately reducing crop productivity. Among these stresses, drought stress has been a major challenge for sustainable crop production and a hot area of research under the current climate change scenario. Organic amendments such as biochar (BC) and compost along with plant growth‐promoting rhizobacteria (PGPR) could be a sustainable strategy to improve crop growth and productivity under drought stress environment. There are several reports about compost, BC, and PGPR application as a single or combined treatment to enhance crop productivity under drought stress. Compost and BC act as conditioners to improve soil physicochemical and biological properties thereby enhancing water holding capacity (WHC) and nutrient retention and availability to the plants. Both BC and compost also serve as carbon sources and suitable environment for PGPR and endogenous microbes to enhance their growth promotion activities under drought stress. PGPR alleviate drought stress via ACC‐deaminase and P‐solubilizing activities, production of phytohormones, secretion of organic acids, acting as biocontrol agents, etc. In the present review, the individual and combined effect of compost, BC, and PGPR to alleviate drought stress in plants has been critically summarized. Moreover, research gaps and future research directions have been identified and discussed in depth.